Non-Abelian three-loop braiding statistics for 3D fermionic topological phases - Jing-Ren Zhou; Qing-Rui Wang; Chenjie Wang; Zheng-Cheng Gu (Nature Communications, 2021)
Non-Abelian statistics plays a crucial role towards realizing topological quantum computation. Here, the authors discover new types of non-Abelian three-loop braiding statistics that can only be realized in 3D interacting fermionic systems.